Beyond kinetic harm and towards a dynamic conceptualization of cyberterrorism - Straub, VJ (ArmisteadTEC LLC, 2021)
After more than two decades of discussion, the concept of cyberterrorism remains plagued by confusion. This article presents the result of an integrative review which maps the development of the term and which situates the epistemic communities that have shaped the debate. After critically assessing existing accounts and highlighting the key ethical, social, and legal dimensions at stake in preventing cyberterrorist attacks, it calls for a more dynamic conceptualization that views cyberterrorism as more abstract, difficult to predict, and hard to isolate; and which embraces a different conception of sufficient harm. In concluding, it proposes a novel definition of cyberterrorism, intended to catalyse a new research program, and sketches a roadmap for further research.